Depression and Quality of Life Among Family Caregivers of Stroke Survivors in Ghana - Abeasi, D.A. (My University, 2014)
The impact on daily lives as a result of stroke is a concern for world health because mostly surviving stroke is an altered life to come for both the survivor and the informal family caregiver. A good proportion of its survivors are left to battle with residual neurological and functional impairment, which often require long term support and care. Mostly after discharge, these stroke survivors depend on family caregivers who are usually ill prepared for their caregiving role. Poor health of the caregiver can in turn affect the general wellbeing of the stroke survivor. Thus, this study examined depression and quality of life among family caregivers of stroke survivors. A sample of one hundred (100) participants was selected purposively using a cross sectional research design at the Korle-Bu Teaching Hospital. The results were analyzed by using Multiple Analyses Of Variance, Multiple Regression Analysis, Independent t-Test, Sobel test and Pearson’s r test to identify the relationships between the variables. The findings were that caregivers experienced significant depressive symptoms and low quality of life than the non caregivers. There was a significant relationship between depression and quality of life. The relationship between social support and quality of life was mediated by depression. Severity of stroke, duration of care, age of caregiver and gender were not significant predictors of depression. The significant predictors of quality of life were financial constraint, age and gender of the caregiver.